PERUBAHAN DAKWAH DI ERA NEW NORMAL DAN TANTANGANNYA (TINJAUAN PERSPEKTIF SOSIOLOGI DAKWAH) - Al Asy'ari (Prodi Sosiologi Agama FIS Universitas Islam Negeri Sumatera Utara, 2020)
The development and advancement of information technology demands a change in activities that originally interacted physically directly turned into virtual meetings. Moreover, since the pandemic, all activities, including preaching that usually gather a large congregation in one place, have started to switch to cyberspace.This research was aimed to design new concept of dakwa’ as respon of new normal era in the sociology perscpective. This research is a library research. Collecting data was conducted by learn some research that has been founded and report of the field from the news. The result of this research conclude some alternation as effect of covid-19 especially in the religion. Three variabel form sociology effect must be respon by the dakwah to sustain the essence of dakwah. And there are two challenge that will be faced of dakwah as the result of new normal era, namely the sociological categorization of the congregation and changes in the socio-economic structure of society which result in changes in habits.